Predictor factors for teacher innovative behavior during curriculum reform: The role of cognitive flexibility, positive affect, and negative affect - Dumbi, Khairunnisa Syafira; Indrasari, Stephanie Yuanita (REID (Research and Evaluation in Education), 2024)
Teacher innovative behavior is a key capability for maximizing teacher performance as well as the student learning process, especially when teachers face new changes in their education system such as curriculum reform. However, insufficient attention has been given to understanding the interaction of predictor factors to encourage teacher innovative behavior. This study aims to assess the role of cognitive flexibility, positive affect, and negative affect in predicting teacher innovative behavior. A cross-sectional and quantitative design was used for this study. The data collection procedure used convenience sampling, with questionnaires distributed online via social media through several teacher communities. Three instruments were used: the Teacher Innovative Behavior Scale, the Cognitive Flexibility Inventory, and the Positive Affect and Negative Affect Schedule. Data were collected from 322 teachers from three educational levels. Descriptive analysis, correlation analysis, and hierarchical multiple regression analysis were conducted. The result showed that cognitive flexibility and positive affect positively predict teacher innovative behavior. On the other hand, negative affect negatively predicts teacher innovative behavior. Regarding the model, the result indicates that cognitive flexibility plays a more crucial role in predicting teacher innovative behavior, explaining 28,1% of the variance in the model. Researchers and policymakers could use the outcome to create future research, policies, and programs to enhance the capabilities of teachers to perform innovative behavior, especially during the educational system’s changes.